Boring sponges, an increasing threat for coral reefs affected by bleaching events. Issue 4 (4th March 2013) - Carballo, José L.; Bautista, Eric; Nava, Héctor; Cruz‐Barraza, José A.; Chávez, Jesus A.
Abstract: Coral bleaching is a stress response of corals induced by a variety of factors, but these events have become more frequent and intense in response to recent climate‐change‐related temperature anomalies. We tested the hypothesis that coral reefs affected by bleaching events are currently heavily infested by boring sponges, which are playing a significant role in the destruction of their physical structure. Seventeen reefs that cover the entire distributional range of corals along the Mexican Pacific coast were studied between 2005/2006, and later between 2009/2010. Most of these coral reefs were previously impacted by bleaching events, which resulted in coral mortalities. Sponge abundance and species richness was used as an indicator of bioerosion, and coral cover was used to describe the present condition of coral reefs. Coral reefs are currently highly invaded (46% of the samples examined) by a very high diversity of boring sponges (20 species); being the coral reef framework the substrate most invaded (56%) followed by the rubbles (45%), and the living colonies (36%). The results also indicated that boring sponges are promoting the dislodgment of live colonies and large fragments from the framework. In summary, the eastern coral reefs affected by bleaching phenomena, mainly provoked by El Niño, present a high diversity and abundance of boring sponges, which are weakening the union of the colony with the reef framework and promoting their dislodgment. These phenomena will probably become even more intense and severe, as temperatures are projected to continue to rise under the scenarios for future climate change, which could place many eastern coral reefs beyond their survival threshold. Abstract : We tested the hypothesis that coral reefs affected by bleaching events are currently heavily infested by boring sponges, which are playing a significant role in the destruction of their physical structure. Forty‐six percent of the more than 10, 000 coral samples examined were invaded by boring sponges, and the results indicated that they are promoting the dislodgment of live colonies and large fragments from the framework, especially in reefs previously impacted by bleaching phenomena.